2021
DOI: 10.1016/j.ejca.2021.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The role of local therapy in the treatment of solitary melanoma progression on immune checkpoint inhibition: A multicentre retrospective analysis

Abstract: Introduction: In patients with metastatic melanoma, progression of a single tumour lesion (solitary progression) after response to immune checkpoint inhibition (ICI) is increasingly treated with local therapy. We evaluated the role of local therapy for solitary progression in melanoma. Patients and methods: Patients with metastatic melanoma treated with ICI between 2010 and 2019 with solitary progression as first progressive event were included from 17 centres in 9 countries. Follow-up and survival are reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Due to this specific attribute, oligoprogressive disease can be treated efficiently with various local therapies, and thereby acquired resistance can be controlled, and we are allowed to continue the previously started, effective systemic therapy. Brain metastases are common in melanoma compared to other malignancies, which may explain why 22 (74%) of our patients were treated for cerebral metastases, but the tumor can often metastasize other peripheral regions ( 6 , 15 , 16 ). The result of several retrospective analyses concluded that some patients treated with checkpoint inhibitors who developed progression had benefited from continuing the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this specific attribute, oligoprogressive disease can be treated efficiently with various local therapies, and thereby acquired resistance can be controlled, and we are allowed to continue the previously started, effective systemic therapy. Brain metastases are common in melanoma compared to other malignancies, which may explain why 22 (74%) of our patients were treated for cerebral metastases, but the tumor can often metastasize other peripheral regions ( 6 , 15 , 16 ). The result of several retrospective analyses concluded that some patients treated with checkpoint inhibitors who developed progression had benefited from continuing the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…First, this seems to be the only prospective study to evaluate the efficacy of SABR after progression to anti-PD-1 in patients with metastatic NSCLC and melanoma. So far, only retrospective series evaluated this (7,9,12). The only prospective trials treated patients with SABR at the start of ICI, to potentially increase response rates by boosting the anti-tumor immunity by radiotherapy (6,13,14).…”
Section: Editorial Commentarymentioning
confidence: 99%
“…To overcome these resistance mechanisms and increase response rates, combination therapies with ICI are investigated. A growing number of reports show that the combination of stereotactic ablative radiotherapy (SABR) and ICI is safe and could increase progression-free survival (PFS) and overall survival (OS) (5)(6)(7)(8)(9). There are even reports of spontaneous regression of non-target lesions, also known as the abscopal effect, possibly due to a synergistic effect between SABR and ICI leading to immunogenic cell death (5,10).…”
mentioning
confidence: 99%
“…Particularly myeloid cells are known to have a complex phenotypic distribution across organs 12 and impact on antitumor immunity 13 14 . Local therapies for oligometastatic progression to extend BRAF or immunotherapy benefit is a clinical strategy in melanoma oncology 15 16 . An unmet need remains for non-invasive biomarkers of lesion and organ-specific response to inform treatment selection and the study of tumor resistance.…”
Section: Introductionmentioning
confidence: 99%